Franciszek Piesik – jedyna polska ofiara muru berlińskiego - Dźwigał, Magdalena (Dzieje Najnowsze, 2015)
Franciszek Piesik – the Only Polish Victim of the Berlin Wall The article commemorates Franciszek Piesik, one of the many victims of the Cold War who after the Second World War sought new opportunities and a „better life” in the West and tried to illegally find themselves on the other side of the Iron Curtain. In many respects the story of the escape by the young Pole in October 1967 is extremely interesting. First, it concerns an attempt at crossing two frontiers of two communist regimes; at the time, the border between East Germany and West Berlin was regarded as the best guarded. The very fact that Franciszek Piesik reached Berlin testifies to his good fortune and a well–devised plan of escape, thus confirming the way in which he tried to reach the free world. Second, in the light of recent research conducted by German historians the instance of a young citizen of People’s Poland killed while attempting to make his way to West Berlin during the post–1961 period is the only known case of the death of a foreigner, a victim from outside East Germany. The text portrays Franciszek Piesik and devotes much attention to the activity of the Polish authorities in connection with interrogations concerning the illegal crossing of the frontier as well as the attitude of the state apparatus to the escapee’s family. Unfortunately, it is impossible to answer satisfactorily all questions about the circumstances and course of the escape endeavoured by the young Pole; nonetheless, the author made every effort to base the contents of the examined question on the most extensive sources.